Regional differences in nitrogen balance and nitrogen use efficiency in the rice–livestock system of Uruguay - Castillo, Jesús; Kirk, Guy J. D.; Rivero, M. Jordana; Haefele, Stephan M. (Frontiers in Sustainable Food Systems, 2023)
The reintegration of crops with livestock systems is proposed as a way of improving the environmental impacts of food production globally, particularly the impact involving nitrogen (N). A detailed understanding of processes governing N fluxes and budgets is needed to design productive and efficient crop–livestock systems. This study aimed to investigate regional differences in N balance (NBAL, defined as all N inputs minus outputs), N use efficiency (NUE, defined as N outputs/inputs × 100), and N surplus (NSURP, defined as all N inputs minus only outputs in food products) in the rice–livestock system of Uruguay. Three regions across Uruguay are distinguished based on soil fertility and length of pasture rotation. The northern region has high soil fertility and short length of rotation (HFSR); the central region has medium soil fertility and medium length of rotation (MFMR); the eastern region has low fertility and long pasture rotation (LFLR). Results for the last 18 years show a very high NUE (90%) for the rice component in all rotations, associated with negative NBALs ranging from −35 kg N ha−1 yr−1 in HFSR to −3 kg N ha−1 yr−1 in LFLR. However, the livestock component, which overall had low animal productivity (<2 kg N ha−1 yr−1), had low NUE (<10%) but positive NBALs in all the rotations, sustaining N supply in the rice component. At the system level, NUE was high (60%) and NBAL was slightly positive in all rotations (from +2.8 kg N ha−1 yr−1 in HFSR to +8.5 kg N ha−1 yr−1 in LFLR). Because of a recent increase in the N fertilizer dose in rice, NSURP for the overall system was intermediate (40 kg N ha−1 yr−1) and should be monitored in the future. Efforts to improve the system's efficiency should focus on the livestock component.